Young Youth Stay Away from Drugs and the Dangers of Underage Marriage - Silfa Hafizah Pulungan (IJCS: International Journal of Community Service, 2023)
Catin who married in Sosopan Village, Kec. Kab. Padang Lawas has increased every year. failure For take continuing education because parents' economic gap is one of the causes of adolescents making the decision to marry even though they are not ready or mature psychologically, mentally and emotionally. Through this socialization activity " Young Youth Stay Away from Drugs and the Dangers of Underage Marriage " it is hoped that students (youth) can continue their education at Public/Private Universities, outside/within the Province and outside/within City Regencies such as STAI Barumun Raya Sibuhuan and take advantage of the time by carrying out productive activities such as participating in activities organized by the village administration.